Hubungan Lingkungan Fisik Rumah dan Kepadatan Hunian dengan Prevalensi Tuberkulosis di Kecamatan Sungai Kunjang Kota Samarinda - Joko Sapto Pramono; Wiyadi Wiyadi (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: The physical environment of the house becomes the main medium of transmission of Mycobacterium Tuberculosis through droplets of tuberculosis patients in the home. The physical environment of the house includes ventilation, lighting and overcrowding.  The highest prevalence of tuberculosis in East Kalimantan Province is Samarinda City. Objective: To determine the relationship between the physical environment of the house and the density of the occupancy with the prevalence of tuberculosis in Sungai Kunjang District, Samarinda City. Method: This type of research was quantitative with a case control design, carried out from August to October 2020 with a population of patients diagnosed with tuberculosis at Loa Bahu, Karang Asam and Loa Bakung Public Health Centers, a total of 57 respondents were taken and 57 respondents as controls. The research instruments were questionnaires and observation sheets. The analysis was carried out by univariate and bivariate using the chy square. Results: There was a significant relationship between the physical environment of the house and the occupancy density with the prevalence of tuberculosis, respectively: home lighting p-value = 0.001 (OR = 3.532), house ventilation p-value = 0.000 (OR = 55.467), occupancy density house p-value = 0.018 (OR = 3.317), and room area p-value= 0.004 (OR = 3.609). Conclusion: There was a relationship between the physical environment of the house and the density of occupancy with the prevalence of tuberculosis.   Education needs to be given to the community in order to physically modify the house to maintain health and avoid transmission of tuberculosis in the home environment.Keywords: Ventilation; lighting; occupancy density; house area; tuberculosis.